Pengaruh Komunikasi Interpersonal Orang Tua Terhadap Perilaku Remaja - Jannah F; Tsuwaibatul Aslamiyah; Ach. Baidowi; Yanto; S. Fathiyatul Jannah (Madaniyah, 2024)
Abstract The research aims to determine the influence of parental interpersonal communication on adolescent behavior in Dusun Tengah, Tlonto Ares Village, Pamekasan. The research employed a quantitative method through a regression test approach. Data were collected from 56 adolescents through the distribution of questionnaires. Hypothesis testing was conducted using the t-test. The research findings indicate that the correlation coefficient of 0.270 suggests a weak relationship between parental interpersonal communication and adolescent behavior. Hypothesis analysis using the t-test reveals a calculated t-value of 2.06, exceeding the critical t-value of 1.68. Therefore, the proposed hypothesis is accepted based on the criterion that if the calculated t-value is greater than the critical t-value, the hypothesis is accepted. The calculation results show that parental interpersonal communication has a 7.29% influence on adolescent behavior. Keywords: Communication, Parents, Interpersonal, Adolescents